2014
DOI: 10.1051/0004-6361/201423539
|View full text |Cite
|
Sign up to set email alerts
|

Dust emission in star-forming dwarf galaxies: General properties and the nature of the submm excess

Abstract: We studied the global characteristics of dust emission in a large sample of emission-line star-forming galaxies. The sample consists of two subsamples. One subsample (SDSS sample) includes ∼4000 compact star-forming galaxies from the Sloan Digital Sky Survey (SDSS), which were also detected in all four bands at 3.4 μm, 4.6 μm, 12 μm, and 22 μm of the WISE all-sky survey. The second subsample (Herschel sample) is a sample of 28 compact star-forming galaxies observed with Herschel in the FIR range. Data of the H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 134 publications
(196 reference statements)
6
37
1
5
Order By: Relevance
“…That there is not much dust-obscured hidden star formation is also implied by the observed thermal freefree cm radio emission in dwarf galaxies with optical and infrared observations. Its flux density is consistent with the value derived from the flux density of the Hβ emission line (Izotov et al 2014b), indicating that there is not a considerable amount of additional star formation, not seen in the UV range, in our galaxies.…”
Section: The Lyman Continuum Escape Fractionsupporting
confidence: 88%
“…That there is not much dust-obscured hidden star formation is also implied by the observed thermal freefree cm radio emission in dwarf galaxies with optical and infrared observations. Its flux density is consistent with the value derived from the flux density of the Hβ emission line (Izotov et al 2014b), indicating that there is not a considerable amount of additional star formation, not seen in the UV range, in our galaxies.…”
Section: The Lyman Continuum Escape Fractionsupporting
confidence: 88%
“…Our results suggest that star formation, and not AGN activity, is responsible for the red WISE colors for the majority of the dwarf galaxy population (also see Izotov et al 2014). We propose a small sample of dwarf galaxy AGN candidates that require follow-up observations to confirm black hole activity.…”
Section: Introductionsupporting
confidence: 52%
“…Low-mass SMBHs that exist in dwarf galaxies power AGNs that have such low luminosities that star formation in their hosts becomes a significant source of contamination. In particular, it has been shown that lowmetallicity dwarf starburst galaxies are capable of heating dust to very high temperatures (Hirashita & Hunt 2004;Reines et al 2008;Griffith et al 2011;Izotov et al 2011Izotov et al , 2014Rémy-Ruyer et al 2015), producing red mid-IR colors. This was recently explored in O'Connor et al (2016), who found that galaxies with low stellar masses have predominantly red WISE colors, which the authors associate with higher specific star formation rates (sSFRs) in these galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Relaño et al (2016) and Reines et al (2008) required an additional ∼ 1000-K blackbody component of "uncertain origin" to fit their observed IR SEDs. Similar excesses, more prevalent in the MIR, have also been observed in a number of blue compact dwarf galaxies (e.g: I Zw 18, II Zw 40, Mrk 930 and Haro 11 (Rémy-Ruyer et al 2015;Vanzi et al 2000;Izotov et al 2014)). Therefore, these observations not only point to the existence of a very hot dust component (∼400-1000 K), but also give compelling evidence for the presence of a persistent (i.e.…”
Section: Snrs Evolving In Sscssupporting
confidence: 63%